O ensino-aprendizagem do português escrito para surdos em pesquisas: análise de resumos acadêmicos (1987-2010) - Botarelli, Geane Izabel Bento (2014)
The deaf education in Brazil is, above all, the scene of major tensions: segregated or inclusive rooms; specialized or regular schools, sign language, or oralism bilingualism; LIBRAS (Brazilian Sign Language) or written Portuguese language etc. As a consequence, researches on the deaf people in academia represent a great amount, summing up 643 works, among master s degree thesis and doctorate s dissertation, within a period of 24 years. For this reason, and considering that the written language acquisition is essential for a qualified school progression, this literature review, guided by quantitative and qualitative methodology, analyzes data from the abstracts available in the CAPES (Coordination of Improvement of Higher Education Personnel) Theses Database, from 1987 to 2010, concerning 136 academic productions whose research was about the teaching and learning of writing in Portuguese language for deaf people, in order to answer who, when, where and how the teaching and learning of written language for deaf people were researched in the Brazilian academic productions. For the analysis, this research was oriented by the contributions of cultural materialism (Williams, 1980), through which it is possible to verify the specifics of material production to interpret the socio-historical practices, and by the Discourse Analysis by Pecheux (2012) and Orlandi (2008), in which we analyze what is said and the unsaid in academic abstracts . It was concluded that this material can help researchers and other interested people to reflect on the research on deaf people held in Brazil. In conclusion, between other things, there is a concentration of papers in states such as São Paulo and in themes such as language and education, usually in programs turned specially to this and also that informations such as the base and theoretical sources are not mentioned in the summaries